Pianificare tra città e campagna (2009)
Agricultural land and woodland in the vicinity of urban settlements appear increasingly to represent a key element and strategic resource for addressing issues of residential quality, and hence the requalification of the urban construct. In effect, from a "vacuum" awaiting construction, the periurban agricultural territory is emerging as the yardstick for a new measurement and integration of the public policies governing urban and territorial plans and those for rural development. This book proposes a number of cues and methodological and operational elements to stimulate reflection on this new scenario. It does so through the exploration of a number of significant and innovative experiences in Italy and the rest of Europe, while at the same time also proposing an initial appraisal of the process of design and social mobilisation for the definition of the scenario for the Prato Agricultural Park.